Hans Kelsen e Carl Schmitt: o debate entre normativismo e decisionismo - Godoy, Paula Véspoli (2010)
The purpose of this work is to analyze the debates between the jurists Hans Kelsen and Carl Schmitt occurred in between wars, during the Weimar Republic. It also purports to consider the theory and the concepts of each author on issues such as democracy, sovereignty, the power of a governor and his limitations, State of Law, strength and function of the Constitution. It analyzes the dualisms involved in this debate, among which, normativism and decisionism, Law and Power, Legal and Political affairs, normality and exception, reflections which eventually led them to the diverse answer on who must be the guardian of the Constitution : the Constitutional Court according to Kelsen s conception and the President of the Reich according to Schmitt s conception. The theoretical accounts of each author regarding the control of law constitutionality, notwithstanding having occurred on the first half of the twentieth century, still bring about studies and fierce criticisms, whether it is due to Kelsen s exacerbated formalism or to Schmitt s reactionary and authoritarian ideology. Many indoctrinators of the Theory and the Philosophy of contemporary Law and Constitutional Law address the subject to deal with the present problems of the constitutional jurisdiction. The criticisms to the formalist normativism, to the state of exception and the demo-liberal parliament model, are amongst the most analyzed issues. The contemporanity of this debate and its importance in the relentless search for the improvement of the control of constitutionality of the law and assurance of the democratic principle and the rights introduced in the Constitution is the goal of the present study